DESIGN IMPROVEMENT OF THE VERTICAL AXIS WIND TURBINE WITH APPLIED FLAPS THROUGH CFD ANALYSIS - Abdulla Khamis; Mohanad Tarek Abdallftah; Mohammed Fares; Salman Shahid; Sharul Sham Dol (Platform, a Journal of Engineering, 2021)
This research aims to optimise VAWT power generation capabilities through the design alteration of blades by the addition of flaps. The application is aimed to be applied in the United Arab Emirates, specifically at Abu Dhabi University campus in Al Ain to replace a margin of the consumed electrical energy (15%) powered by the typical nonrenewable energy means. To study the effects of design alteration, relevant design parameters on the aerodynamic properties of the wind turbine, a typical standard design with standard dimensions were considered and used as a benchmark for comparison. Two aerodynamic simulation software were adopted, namely ANSYS FLUENT and QBlade, while the designs were drawn through AutoCAD. As per the simulation results, the addition of flaps resulted in an overall increase of 3.11% in power generation. The simulation results were then scaled up using dynamic similarity to obtain a total power consumption of 6 kW for each turbine suggesting that the newly built Al Ain campus would require 43 turbines to cover 15% of the total electricity consumption in a year. The building of a control system for active pitch control was not feasible due to increased complexity.